2007
DOI: 10.1590/s0004-27302007000900016
|View full text |Cite
|
Sign up to set email alerts
|

Redução da densidade mineral óssea em mulheres na menacme com prolactinoma

Abstract: RESUMOA hiperprolactinemia tumoral e conseqüente hipogonadismo têm sido associados à osteoporose. Avaliamos a densidade mineral óssea (DMO) por absortometria com dupla fonte de RX em 24 mulheres entre 18 e 49 anos, com prolactinoma (15 macro e 9 micro). Utilizamos teste t de Student não pareado ou Mann-Whitney para comparar subgrupos, e teste de Spearman para correlações. O maior acometimento foi de coluna lombar, onde 20,83% das pacientes tinham Z-escore ≤ -2 DP. Não detectamos diferenças densitométricas entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…To date, and to our knowledge, few data are available on the impact of hyperprolactinemia on bone metabolism in children and adolescents [20]. In adult patients, discussions are ongoing on the possibility of a direct effect or an effect mediated via hypoestrogenism [21,22]. Colao et al [23] found significantly lower values of bone mineral density in adolescent patients with hyperprolactinemia than in their sex- and age-matched controls and also lower bone mineral density values corrected for age in the adolescent patients with hyperprolactinemia than in the young adult patients.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…To date, and to our knowledge, few data are available on the impact of hyperprolactinemia on bone metabolism in children and adolescents [20]. In adult patients, discussions are ongoing on the possibility of a direct effect or an effect mediated via hypoestrogenism [21,22]. Colao et al [23] found significantly lower values of bone mineral density in adolescent patients with hyperprolactinemia than in their sex- and age-matched controls and also lower bone mineral density values corrected for age in the adolescent patients with hyperprolactinemia than in the young adult patients.…”
Section: Clinical Featuresmentioning
confidence: 99%